Worker health in Intensive Care Units: Trends in brazilian scientific production (Research, Society and Development, 2021)
The aim of the study was to identify trends in scientific production, in theses and dissertations, on occupational health in intensive care units. This is a narrative-type review. The survey of productions took place in May 2020 with an online search in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES) using the words "worker health" AND "intensive therapy". After the application of selection criteria, a total of 36 productions were included for analysis. In the results, it was possible to identify that most of the productions were dissertations from master's courses in nursing, from the southeastern region of Brazil and after the year 2012. The studies were predominantly used with nursing workers, including neonatal, pediatric and adult ICUs. The highlighted themes are characteristic of intensive care work and health professions, as well as the occupational risks that are present in the daily lives of ICUs. In the final remarks, we emphasize that in the analyzed productions, the constant and important relationship between the influence of work activities and the health of workers in intensive care units was evident.